2022
DOI: 10.1093/oncolo/oyab043
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor-related New-onset Thyroid Dysfunction: A Retrospective Analysis Using the US FDA Adverse Event Reporting System

Abstract: Objectives The study aimed to investigate the prevalence and demographic characteristics of an immune checkpoint inhibitor (ICI)-related thyroid dysfunction (ICI-TD), and to explore risk factors of poor clinical outcome using data from the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS). Methods This is a retrospective study. All cases, aged over 18-year olds, of new-onset or new-diagnosed thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In our data set, there was a rare incidence of Grade 3 hypothyroidism and of hyperthyroidism events (0.2%). A retrospective analysis of the US Food and Drug Administration adverse event reporting system reported that 9.3% (171/1842) of patients presented with hyperthyroidism before hypothyroidism ( 29 ). Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…In our data set, there was a rare incidence of Grade 3 hypothyroidism and of hyperthyroidism events (0.2%). A retrospective analysis of the US Food and Drug Administration adverse event reporting system reported that 9.3% (171/1842) of patients presented with hyperthyroidism before hypothyroidism ( 29 ). Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…Liothyronine, being classically used to treat hypothyroidism, could be useful to reduce the risk of irAEs of the thyroid caused by anti-PD-1 mAbs. Nevertheless, the potential use of liothyronine in combination with an ICI would require careful and regular monitoring of thyroid functions, as is already the case for different immune checkpoint inhibitor therapies [ 45 ].…”
Section: Drug Repositioning To Target the Pd-1/pd-l1 Checkpointmentioning
confidence: 99%
“…The incidence and manifestations of each ICI-related endocrinopathy are listed in Table 2 . [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] ICI-induced APS is even rare. In our previous study, the likelihood of APS in patients on combination therapy of anti-CTLA-4 and anti-PD-1 increased onefold than in patients on PD-1 inhibitors and fourfold than in those on PD-L1 inhibitors.…”
Section: Clinical Manifestations Of Ici-related Endocrinopathiesmentioning
confidence: 99%
“…In our previous study, the likelihood of APS in patients on combination therapy of anti-CTLA-4 and anti-PD-1 increased onefold than in patients on PD-1 inhibitors and fourfold than in those on PD-L1 inhibitors. [ 32 ]…”
Section: Clinical Manifestations Of Ici-related Endocrinopathiesmentioning
confidence: 99%
See 1 more Smart Citation